Consolidation behaviour of thick suspension in centrifugal dewatering with and without supernatant - Fukuyama, Ryo; Jami, Mohammed Saedi; Tanaka, Takanori; Iwata, Masashi (Elsevier Inc., 2015)
This study proposes an analytical method considering the consolidation behaviour in centrifugal dewatering of compressible filter cake. The main focus is on the consolidation behaviour after the disappearance of the supernatant in centrifugal dewatering of thick suspension. Solving the consolidation equation under the boundary condition proposed in this study, which represents the no flow rate due to the stable meniscus at the cake surface, it is possible to describe the shrinkage of the cake after the disappearance of the supernatant. Moreover, the analytical results show that, after the disappearance of supernatant, the meniscus at the cake surface plays an important role on the drastic increase of the solid compressive pressure near the surface and it has been clarified that the shrinkage of the cake mainly occurs near the surface.